B
已知全集U={0,1,2,3,4},M={0,1,2},N={2,3},则(C U M)∩N= [
1个回答
相关问题
-
已知全集U={0,1,2,3,4,5},集合M={0,3,5},M∩(C U N)={0,3},则满足条件的集合N共有
-
(2014•南昌二模)已知全集U={-2,-1,0,1,2,3},M{-1,0,1,3},N{-2,0,2,3},则(∁
-
已知全集U=R,集合 M={x|x≥1},N={x| x+1 x-2 ≥0} ,则 C U (M∩
-
已知全集U={1,2,3,4,5,6,7,8},M={1,3,5,7},N={5,6,7},则C u (M∪N)= [&
-
设全集U=R,集合M={x|-2≤x<3},N={x|-1≤x≤4},则N∩C U M= [
-
已知全集U={1,2,3,4,5,6,7,8},M={1,3,5,7},N={5,6,7},则(u(M∪N)=
-
{.已知全集U={1,2,3,4,5},集合M={1,2,3},N={3,4,5},则M∩(ðUN)=( )
-
已知全集U={1,2,3,4,5,6},M={2,3,5},N={4,5},则集合{1,6}=( ) A.M∪N B.
-
已知全集U=R,集合M={x|x2-2x-3≤0},N={y|y=3x2+1},则M∩(∁UN)=( )
-
(2013•兰州一模)设全集U={1,2,3,4,5},已知U的子集M、N满足集M={1,4},M∩N={1},N∩(∁